Leninza ETHNICITY, LANGUAGE AND CULTURE: ETHNICITY, LANGUAGE AND CULTURE - Masharipova, Leninza (Журнал иностранных языков и лингвистики, 2022)
Nationality is the identity of an individual’s nation where he/she is given a birth, while ethnicity is the identity of a subgroup to which he/she comes from. Individuals of the same nation may have a various ethnicity and people of the same ethnicity can belong to distinguished nations.